Suppression of ACE2 SUMOylation protects against SARS-CoV-2 infection through TOLLIP-mediated selective autophagy - Shouheng Jin; Xing He; Ling Ma; Zhen Zhuang; Yiliang Wang; Meng Lin; Sihui Cai; Lu Wei; Zheyu Wang; Zhiyao Zhao; Yaoxing Wu; Lin Sun; et al. (Nature Communications, 2022)
SARS- CoV-2 hijacks ACE2 for cell entry. Here, the authors report that dynamic SUMOylation modulates the TOLLIP-directed selective autophagic degradation of ACE2 and suggest SUMOylation inhibition as a potential intervention against SARS-CoV-2 infection.